Food safety - Merino, Noel. (Farmington Hills, MI : Greenhaven Press, 2012)
'Food Safety: Does the Current US System Ensure Food Safety?; Are New Food Technologies Safe?; Are Certain Foods Unsafe to Eat?'--Provided by publisher.
Keywords: Food adulteration and inspection -- United States; Food industry and trade -- United States -- Safety measures; Food -- Biotechnology -- Safety measures